Climate Change as a Human Rights Issue: Litigating Climate Change in the United Nations Human Rights Committee - Akindele, Adeniyi (Faculty of Law, Universitas Negeri Semarang, 2023)
This paper delves into the convergence of climate change and human rights, with a specific focus on the avenue of litigation within the United Nations Human Rights Committee (UNHRC). In recent years, the escalating impacts of climate change have posed significant threats to human rights, including the rights to life, health, food, water, and a healthy environment. Recognizing the urgency of addressing these challenges, there is a growing discourse on utilizing human rights mechanisms to hold states and other actors accountable for their contributions to climate change and their failure to mitigate its effects. By examining pertinent legal frameworks, including international treaties such as the International Covenant on Civil and Political Rights (ICCPR) and the International Covenant on Economic, Social and Cultural Rights (ICESCR), alongside evolving case law and emerging legal strategies, this paper evaluates the potential for leveraging the UNHRC as a forum for litigating climate change as a human rights issue. It scrutinizes the complexities, obstacles, and opportunities inherent in such litigation, emphasizing its potential to advance climate justice and bolster accountability. Ultimately, this paper underscores the imperative of reframing climate change as not solely an environmental concern but also a profound human rights imperative. By advocating for the recognition of individuals' rights in the face of climate change impacts, litigating before the UNHRC offers a promising avenue for driving systemic change, safeguarding vulnerable communities, and fostering a more equitable and sustainable future.